Initial Validation and Findings From the Willing/Ready Subscale of the Church Addiction Response Scale - Clements, Andrea D.; Cyphers, Natalie; Whittaker, Deborah L.; McCarty, Brett (Frontiers in Psychology, 2021)
Addiction has been a global health crisis over recent decades and worsened substantially during COVID-19 lockdowns. We report on the development, validation, and findings from an instrument developed to assess the readiness of churches in the Appalachian Highlands to address addiction. The Church Addiction Response Scale (CARS) is a 41-item, three section measure assessing “What are your views about addiction?” (14 items), “What are your views about interacting with people who are addicted to drugs?” (11 items), and “What do you think the church’s role is in addressing addiction?” (16 items). The CARS was found to be unidimensional with strong internal consistency and initial evidence of construct validity was positive. Most respondents reported willingness to assist people living with addiction, but many reported that they felt underprepared, thus were not ready. Areas of preparation were largely those that could be addressed through training, such as understanding the physiology and psychology of addiction, available treatment options, and how to avoid doing harm. Thus, with adequate training, the likelihood of equipping a church-based workforce to provide support for people living with addiction seems attainable.